Prototipo de vivienda productiva rural (desierto de la Tatacoa, Villavieja - Huila) (2020)
The Project of Investigation propuse a Prototype of rural housing in La Tatacoa desert, for the population who live in the rural zone of Villavieja-Huila. According to important aspects to consider as Economic, Culture, Social, environmental and structural been identified in the place, aprovide a suitable construction model in the Tatacoa’s desert, in which decrease the negative impacts and converted to the ecosystem. Likewise also developing an methodology base on the Urban-regional analysis in order to study these problem since diffrentes points of view. This Project find to optimize rural dwelling by means of self-sustainability and provide on bioclimatic strategies, technologies and craft kind, in order to mitigate the impacts caused on environment for not suitable constructions, adapt to global warming, improving quality life of the rural population and uplifting the strand of the place.